Comparative evaluation of echocardiographic characteristics of the heart left ventricle in female and male rats - E. O. Ionova; E. I. Barchukova; M. B. Vititnova; I. B. Tsorin; S. A. Kryzhanovskii (LLC "Publisher OKI", 2021)
The aim of the present study is a comparative assessment of the echocardiographic characteristics in female and male mongrel rats. In experiments on anesthetized rats (ketamine 100 mg / kg, iv), it was shown that in female rats, the size and volume of the left ventricle are smaller than in males, but compared with males, their left ventricular ejection fraction, which characterizes its inotropic function, is statistically significantly higher.